Resposta :
Se
A = x - y
B = x + y
temos:
A² - B²
(x - y)² - (x + y)²
(x² - 2xy + y²) - (x² + 2xy + y²)
x² - 2xy + y² - x² - 2xy - y²
= - 4xy
Espero ter ajudado
Resposta:
[tex]\textsf{Leia abaixo}[/tex]
Explicação passo a passo:
[tex]\mathsf{A = x - y}[/tex]
[tex]\mathsf{B = x + y}[/tex]
[tex]\mathsf{A + B = 2x}[/tex]
[tex]\mathsf{A - B = -2y}[/tex]
[tex]\mathsf{A^2 - B^2 = (A + B) \times (A - B)}[/tex]
[tex]\mathsf{A^2 - B^2 = 2x \times (-2y)}[/tex]
[tex]\boxed{\boxed{\mathsf{A^2 - B^2 = -4xy}}}[/tex]